PERLINDUNGAN HARIMAU SUMATERA DI KABUPATEN ACEH TENGGARA - Yuliannova Lestari; Efendi Efendi (Fakultas Hukum Universitas Syiah Kuala, 2017)
Abstrak - Pasal 21 ayat (2) Undang-Undang Nomor 5 Tahun 1990 tentang Konservasi Sumber Daya Alam Hayati dan Ekosistemnya menyebutkan bahwa setiap orang dilarang untuk menangkap, melukai, membunuh, menyimpan, memiliki, memelihara, mengangkut, dan memperniagakan satwa yang dilindungi dalam keadaan hidup dan mati. Akan tetapi pada kenyataannya di Kabupaten Aceh Tenggara masih terjadi perburuan dan perdagangan ilegal terhadap satwa yang dilindungi berupa Harimau Sumatera (Phantera tigris sumatrae). Untuk itu penting kiranya untuk diteliti tentang perlindungan Harimau Sumatera (Panthera tigris sumatrae) di Kabupaten Aceh Tenggara.Hasil penelitian menunjukkan bahwa pemerintah belum optimal dalam melakukan perlindungan terhadap Harimau Sumatera (Panthera tigris sumatrae) dan habitatnya seperti yang telah di atur dalam UU No. 5 Tahun 1990. Hal ini dikarenakan kurangnya jumlah PPNS di BKSDA Aceh, kurangnya kemampuan sumber daya manusia, tidak adanya tempat karantina dan rehabilitasi, serta kurangnya kesadaran masyarakat.Kata Kunci : Perlindungan, Harimau sumatera Abstract - The purpose of this study is to describe the factors that resulted in a conviction of forgery of Motor Vehicle registration number, obstacles in the process of resolving the crime of falsification of Motor Vehicle registration number and resolution efforts against counterfeiting of Motor Vehicle registration number. The results showed that the actors did it all caused by economic factors, environmental factors and factors of interest in motor vehicle demand in the market that does not comply with the people's purchasing power. Barriers faced by members of the Traffic Unit in the process of completion falsification of Motor Vehicle registration number includes the lack of understanding of most people's Motor Vehicle registration number is false, the lack of thoroughness of the police and criminal networks. The resolution attempts against criminal counterfeiting Letter Number of motor vehicles includes the completion of the pre-entif, preventive and repressive. Suggested to Langsa Police Traffic Unit in order to educate more people about the understanding of Motor Vehicle registration number of the original and also provide training to police officers on procedures Langsa Police Vehicle registration number to distinguish genuine and fake motor.Keywords : The Crime Of Falsification, Motor Vehicle Registration Number.